Collective efficacy at the Rugby World Cup 2015 - The role of imagery and observation - Shearer, D. A. (European Journal of Sport Science, 2015)
The Rugby World Cup in 2015 will present each competing team with unique psychological challenges not usually encountered in normal international fixtures. In the "pressure-pot" environment of the tournament, teams that have the strongest sense of collective efficacy will most likely perform to their best and respond positively to the outside stressors (e.g., media interest, public expectations). In this review, the importance of collective efficacy to team performance at the World Cup in terms of team resiliency and minimising process losses is discussed. In addition, the relationship between collective efficacy and other psychological factors such as team cohesion is highlighted. From a practical perspective, an introduction to interventions to develop collective efficacy is provided. In particular, the neuroscience evidence for the use of imagery and observation interventions to improve individual collective efficacy perceptions is highlighted. It is emphasised how these interventions are particularly suited to international teams who compete together sporadically. Finally, specific recommendations are made such that practitioners might be able to implement these strategies with their teams before the World Cup.